Pendampingan Pemanfaatan lahan Pekarangan Di Desa Banjararum Kecamatan Kalibawang Kabupaten Kulon Progo - Silvi Nur Oktalina Oktalina; Wiyono Wiyono; Rochmad Hidayat (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
Home garden is a land that is around the house. Home garden is widely used by the owners to plant crops, plantations, fruits and timber crops. Plantation in home garden usually in intercropping. The width of the ownership of the homegarden in Kulon Progo Regency is relatively narrow, but the community has local wisdom to utilize the home garden by combining various types of plants so that it can give the result and increase the family income. This community devotion activity is done with the aim to give assistance of Banjararum Village community in utilizing home garde so that it can be more productive with limited area of land owned by society. This activity is done through training the utilization of home garden with cultivation of agricultural crops in theory and then practice the knowledge gained by making demonstration plot. The demonstration plot is focused in Dondong hamlet as a pilot area. Strengthening the marketing network is done in cooperation with PT East West Indonesia as one of the producers of agricultural crops. The result of this community service activity is the increasing knowledge of the people of Desa Banjararum in utilizing the yard land so that it can increase the family income. The community also acquired a new network of seed producers involved in community service activities.